Biomass properties from different Miscanthus species. (2nd May 2013) - Liu, Chenchen; Xiao, Liang; Jiang, Jianxiong; Wang, Wangxia; Gu, Feng; Song, Dongliang; Yi, Zili; Jin, Yongcan; Li, Laigeng
Abstract: Miscanthus, a peculiar genus originating from East Asia, has been considered a promising type of gramineous plant for the bioenergy industry. In this study, four major Miscanthus species widely distributed in China, Miscanthus sinensis, Miscanthus floridulus, Miscanthus sacchariflorus, and Miscanthus lutarioriparius were assessed for their biomass production, chemical composition, and saccharification efficiency. Results show that the annual dry biomass yields of M. sinensis, M. floridulus, M. sacchariflorus, and M. lutarioriparius averaged 16.7, 22.5, 16.7, and 32.0 t ha −1 over 3 years, respectively. M. sinensis and M. floridulus have similar chemical compositions, but different from M. sacchariflorus and M. lutarioriparius . The efficiencies of enzymatic saccharification were assayed after pretreatment with dilute acid and green liquor, respectively. The M. sinensis and M. floridulus biomass displayed higher saccharification efficiency in the case of dilute acid pretreatment, while the M. sacchariflorus and M. lutarioriparius biomass showed higher efficiency following the green liquor pretreatment. Furthermore, a rapid estimation model for predicting Miscanthus biomass saccharification efficiency was established on the basis of near‐infared reflectance spectrometry analysis. Abstract : Miscanthus has been considered a potential energy crop for lignocellulosic biomass production. Four Miscanthus species widely distributed in China were assessed for their biomass production, chemical composition, and saccharification efficiency.